Redes e sociabilidades na Modernidade Tardia - Fontes, Breno Augusto Souto (Latitude, 2022)
This brief essay objectivates analyze the diverse research agendas guided from the thematic trajectories of social networks and sociability. It illustrates quite clearly a wide range of issues of contemporary social sciences: media and cultural contexts, technological innovations, globalization, migrations and sociability, organizations, health and sociology of science - working in the social processes underlying the construction of the disciplinary field of social networks. Of particular interest is the construction of sociability mediated by the internet, online media communication platforms, possible for private business establishments with various actors in communication from conversation rooms, with the possibility of facing the face experienced by the internet. They are, as we see approaches that stand out for their actuality, and for how much they are built from the sociology of social networks, original. Important examples of the development of this increasingly relevant research agenda are the approach of users from the reticular structure anchored to the mediation of virtual development technology.